Short-time effects of herbicide nicosulfuron on biochemical activity of chernozem soil - Radivojević Ljiljana (Journal of the Serbian Chemical Society, 2012)
Short-time effects of the herbicide nicosulfuron on biochemical activity of soil was investigated. Nicosulfuron rates of 0.3, 1.5 and 3.0 mg/kg of soil were tested in a laboratory on chernozem soil. Dehydrogenase activity, change in microbial biomass carbon, soil respiration and metabolic coefficient (qCO2) were examined. Samples were collected for the analysis 1, 7, 14, 21, 30 and 60 days after nicosulfuron application. The obtained results indicated that the effect of nicosulfuron on soil biochemical activity depends on its application rate and duration of activity, and the effect was either stimulating or inhibiting. However, the changes detected were found to be transient, and therefore there is no real risk of the compound disrupting the balance of biochemical processes in chernozem soil.